IS 26. Transcranial magnetic stimulation (TMS) and functional magnetic resonance imaging (fMRI) - Siebner, H.R. (Clinical neurophysiology, 2013)
The combination of transcranial magnetic stimulation (TMS) and functional magnetic resonance imaging (fMRI) is a powerful multimodal approach to study human brain function. fMRI uses the blood oxygen level dependent (BOLD) signal to map changes in regional neural activity at high spatial resolution. When TMS is interleaved with fMRI (online approach), it is possible to assess how focal cortex stimulation acutely modifies the activity and connectivity in the stimulated neuronal circuits. By manipulating the “neural state” of the cortical target area, one can examine how a change in context alters the regional and distributed BOLD response to TMS. TMS and fMRI can also be separated in time (offline approach). A conditioning session of repetitive TMS (rTMS) may be used to induce rapid reorganization in functional brain networks. The temporospatial patterns of TMS-induced reorganization can be subsequently mapped using fMRI. Alternatively, fMRI can be performed before TMS to localize brain areas that are involved in a given task. The temporospatial activation pattern obtained by neuroimaging can then be used to define the optimal site of stimulation for subsequent TMS. In this lecture, I will address some general methodologic issues that need to be taken into account when combining TMS and fMRI. I will then discuss how the combination of fMRI and TMS can be used to study the selection of actions in the human brain.